2017
DOI: 10.1111/1753-6405.12702
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of intentional self‐poisoning from New Zealand national registry data

Abstract: Objective: Understanding which population groups intentionally poison themselves by overdose and which substances are used are key to developing prevention efforts for such injuries. This paper uses Ministry of Health (MOH) data to explore the demographic characteristics of those who intentionally self-poison and the substances used, identifies limitations of existing data collections and makes recommendations for the future. Methods: MOH mortality data from 2000 to 2012, and public hospital presentation data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
2
8
1
Order By: Relevance
“…However, our examination of patients with severe intoxication indicated that sex was unrelated to survival. The incidence of severe intoxication among different age groups also varied in previous studies (17,23,27). We found that elderly patients were more likely to die from severe intoxication.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…However, our examination of patients with severe intoxication indicated that sex was unrelated to survival. The incidence of severe intoxication among different age groups also varied in previous studies (17,23,27). We found that elderly patients were more likely to die from severe intoxication.…”
Section: Discussionsupporting
confidence: 48%
“…Our overall in-hospital mortality rate was much higher than reported in other countries (Taiwan: 2.6%, other countries: 0.1-1.3%), as was our mortality rate from severe intoxication (Taiwan: 21.6%, other countries: 2-9%) (1, 2, 14, 15). The most likely reason is the higher proportion of severe intoxication events or greater severity of intoxication in our population (5)(6)(7)(8)(9)(10)(11)(12)(13)(16)(17)(18). Our mean ICU stay (3 days) and hospital LOS (7 days) was longer than reported in studies from The Netherlands and Hong Kong (ICU: 0-1.3 days; hospital LOS: 1-3 days) (14,18,19).…”
Section: Discussionmentioning
confidence: 47%
“…These codes record broad groups of medicines, but not specific substances. 2 Further, there is no information collected on how or where the substance was obtained. International evidence suggests that ease of access is key to substance selection in intentional selfpoisoning, and although people may choose to take medicines prescribed to someone else if they gain access, most use their own prescribed medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Intentional self-poisoning (ISP) where too much of a medication or other substance is taken by a person for the purpose of self-harm is a common type of injury treated in Emergency Departments in New Zealand, with paracetamol (acetaminophen) commonly involved [1]. Paracetamol is commonly encountered in exposures also in, for example, Australia [2][3][4], Ireland [5][6][7], England [8], Canada [9,10], and the United States [11].…”
Section: Introductionmentioning
confidence: 99%
“…Poisoning fatalities in general occur at an annual rate of 7.1/100,000 population in New Zealand, and 71% of them are intentional [12]. Hospital admissions due to poisoning occur at an annual rate of 115.4/ 100,000 in New Zealand, and again 65% of such presentations are due to ISP [12], with an annual rate of 70.86 hospital presentations per 100,000 population for suspected ISP [1]. Rates of hospital presentations may not be directly comparable internationally due to differences in definitions and methodologies, e.g.…”
Section: Introductionmentioning
confidence: 99%